Doing visual ethnography images, media and representation in research - Pink, Sarah 1966- (Sage, 2001)
This text explores the use and potential of photography, video and electronic media in ethnographic and social research. The book has a reflexive approach to the theoretical, methodological, practical and ethical issuesfor using media.
Keywords: Anthropologie visuelle; Culturele antropologie; Ethnologie - Méthodologie; Onderzoek; Visuele informatie; Ethnology -- Methodology; Visual anthropology; Visuelle Medien; Ethnologie